PENERAPAN PERUBAHAN UKURAN MATA JARING DALAM PENANGKAPAN IKAN TERBANG SECARA BERKELANJUTAN DI KECAMATAN SENDANA KABUPATEN MAJENE - Najamuddin Najamuddin; Andi Assir; Mahfud Palo; Andi Asni Najamuddin (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2018)
Catching flying fish in Sendana Majene Subdistrict is carried out continuously with gill nets 1-1.5 inches. The catch of flying fish is mostly still young fish (not yet worth catching). The demand for flying fish is quite high due to the existence of special stalls of smoke fly fish around fishing settlements. Apart from smoke flying fish, dried flying fish are also sold as souvenirs. Therefore, fishermen will continue to increase production. Various results of research and field observations show that gill net is able to catch flying fish well but the size of fish caught is dominated by young fish. The effort to increase the net mesh size to 1.5 inches resulted in the diminishing number of young flying fish. Catching flying fish in Majene waters is generally carried out with drifting gill nets with mesh sizes of 1 and 1.25 inches which are very intensive every fishing season while L50 (11.92 cm) and Lm (13.59 cm) for 1 inch more net mesh size were smaller compared to the length of the first gonad maturity, in this case most of the catch is still classified as young fish (Palo, 2009). Partners are a group of flying fish fishermen. Partner problems, flying fish production is getting smaller, group capacity is not strong and group management is still weak. Partners have not been able to obtain assistance facilities from various community empowerment programs carried out by the government. The approach to be used in this service includes: identification, observation, counseling, demonstration, construction, application, assistance, field observation and evaluation monitoring. Indicators of the success of activities are measured based on the results of the application of technology compared to the results of fishing gear commonly used by fishermen. Implementation of service includes counseling, construction of fishing gear, fishing operations and assistance has been going well. The size of 1.5-inch mesh is only able to catch flying fish in a limited amount, while the size of the 1.25-inch mesh can catch flying fish in relatively large numbers. Flying fish caught with 1.25-inch mesh size has passed the size of the first gonad mature so that it supports sustainable fisheries.